2011
DOI: 10.1007/s00704-011-0459-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of the Buenos Aires, Argentina, urban heat island

Abstract: This paper describes the statistical characteristics and temporal variability of the urban heat island (UHI) intensity in Buenos Aires using 32-year surface meteorological data with 1-h time intervals. Seasonal analyses show that the UHI intensity is strongest during summer months and an "inverse" effect is found frequently during the afternoon hours of the same season. During winter, the UHI effect is in the minimal. The interannual trend and the seasonal variation of the UHI for the main synoptic hours for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 26 publications
2
31
0
1
Order By: Relevance
“…According to other studies (e.g. Oke 1987;Hage 1972;Camilloni and Barrucand 2012;Erell andWilliamson 2007, Holmer et al 2007;Linden 2011;Bohnenstengel et al 2011), maximum UHI intensity is observed around 3-5 h after sunset although there are also studies which show that the maximum intensity can be observed just before sunrise (e.g. Jauregui et al 1992;Fortuniak and Kłysik 1998).…”
Section: Measurement Datamentioning
confidence: 89%
“…According to other studies (e.g. Oke 1987;Hage 1972;Camilloni and Barrucand 2012;Erell andWilliamson 2007, Holmer et al 2007;Linden 2011;Bohnenstengel et al 2011), maximum UHI intensity is observed around 3-5 h after sunset although there are also studies which show that the maximum intensity can be observed just before sunrise (e.g. Jauregui et al 1992;Fortuniak and Kłysik 1998).…”
Section: Measurement Datamentioning
confidence: 89%
“…The UHI effect is mainly a night time warming effect. This is generally acknowledged by some studies that also refer to the cooling effects, which are also called an 'inverse' UHI, that the UHI may represent during the day (i.e., UHI < 0 • C) [58][59][60]. This is particularly true for summer, which is the season considered here to study HWs.…”
Section: The Urban Heat Island and Heat Wavesmentioning
confidence: 91%
“…When considering the longitudinal effect, the years when AH has a most eastwards shift in spring (Figure 4a 1986, 1990, 1992, 1995, 1996, 1998, 2000, 2001, 2006, 2007, 2011, 2012 1979, 1981, 1982,1984, 1985, 1993, 1994, 1997, 2002, 2003, 2009 AALAT −0.569 0.481 1979, 1981, 1984, 1989, 1991, 1993, 1994, 1995, 2003, 2005, 2008, 2009, 20111980, 1982, 1985, 1986, 1988, 1990, 1997, 1998, 1999, 2000, 2001, 2004, 2006, 2007, 2010AALON −0.289 0.529 1979, 1980, 1982, 1985, 1987, 1989, 1991, 1993, 1997, 2002, 2004, 2006, 2008, 20091981, 1983, 1986, 1992, 1994, 1996, 2000, 2003, 2007, 2010…”
Section: Springmentioning
confidence: 99%